Antimicrobial activity of Saraca indica against clinical pathogens - Hema TA; Parvathy J; Shiny M; S.Sujatha (International Journal of Phytomedicine, 2012)
The antimicrobial activity of flowers of the medicinal plant Saraca indica collected from from the regions of Ambalathara, Kerala, South India was checked against the clinical pathogens by well diffusion method. Saraca i1ndica showed highest antimicrobial activity on methanolic extracts. The phytochemical evaluation showed the presence of alkaloids, tannins, proteins and reducing sugars. With the help of column chromatography the methanolic extract was purified and highest antimicrobial activity was observed in the concentration 2:8. By thin layer chromatography the compounds are separated and the Rf value obtained was 0.6. The compound responsible for the antimicrobial activity was partially identified as alkaloids